DAKWAH, KESENANGAN, DAN SENSE OF COMMUNITY: SAHABAT HIJRAH PEKANBARU - Dony Arung Triantoro; M. Alam Zumiraj (Harmoni, 2021)
The topic of fun among Indonesian moslem youth has long been a serious concern for a some of scholars. In several academic studies, fun is often seen as a single variable that has not Islamic tendency, so that fun is considered to endanger the morality of youth. In short, fun culture of Indonesia’s youth is described as a moral panic discourse. This opinion is increasingly finding its momentum when previous studies discussing Islamist groups such as the Salafi managed to find an anti-fun narrative that was echoed by them. However, recent studies have shown that Salafis are also involved in pleasurable activities. This paper does not discuss about fun in the Salafi group, but criticizes previous views which always view fun as a moral panic discourse among youth. It is true that in some cases fun becomes a moral decay source for youths, but in other cases, fun also becomes an instrument for Moslem youth to disseminate Islamic discourse and others. Borrowing the concept of ‘Islamic fun’ from Asef Bayat, this paper explores about the culture of fun among moslem youth in Pekanbaru. This article aims to determine: First, to find out how the Sahabat Hijrah Pekanbaru community uses fun as an instrument of da’wah among moslem youth in Pekanbaru. Second, knowing how moslem youth in Pekanbaru negotiate their Islamic identity through fun activities. Third, knowing the extent to which fun is appropriated into youth da’wah activities such as Sahabat Hijrah community. Finally, this study aims to determine fun as social capital to strengthen the sense of community among moslem youth in Pekanbaru. Through fieldwork (ethnography) by studying data through observation, personal communication and documentation, this article shows that fun and Islam in the Sahabat Hijrah community are related with each other and are continuously negotiated by their followers.